2019
DOI: 10.1111/jcpt.13071
|View full text |Cite
|
Sign up to set email alerts
|

Elevation in serum uric acid levels predicts favourable response to erlotinib treatment in patients with metastatic non‐small‐cell lung cancer

Abstract: What is known and objective Erlotinib is a small molecule tyrosine kinase inhibitor which blocks the activation of epidermal growth factor receptor (EGFR), a transmembrane receptor that is upregulated in many cancer types. Inhibition of angiogenesis with consequent impairments in intratumoral microcirculation is one of the mechanisms through which EGFR inhibition halts the progression of cancer. A consequence of impaired microcirculation is intratumoral hypoxia, which results in increases in serum uric acid le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In addition, erlotinib is also a RTK inhibitor, which inhibited the activation of epidermal growth factor receptor (EGFR), and has been administrated to treat many cancers. It exerted its antitumor function by inhibiting angiogenesis and consequently impairing intratumoral microcirculation [78]. Another research group established an EGFR-overexpressing clear cell ovarian carcinoma PDX, and indicated that erlotinib markedly reduced tumor weight in this model [38].…”
Section: Rtk Inhibitormentioning
confidence: 99%
“…In addition, erlotinib is also a RTK inhibitor, which inhibited the activation of epidermal growth factor receptor (EGFR), and has been administrated to treat many cancers. It exerted its antitumor function by inhibiting angiogenesis and consequently impairing intratumoral microcirculation [78]. Another research group established an EGFR-overexpressing clear cell ovarian carcinoma PDX, and indicated that erlotinib markedly reduced tumor weight in this model [38].…”
Section: Rtk Inhibitormentioning
confidence: 99%